Pengaruh Implementasi ISO 9001 : 2015 terhadap Performa Performa Perusahaan (Studi Kasus Industri Garam Konsumsi Beryodium) - Putri, Karina; Derriawan; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2021)
The purpose of this study was to determine the effect of the implementation of the ISO 9001: 2015 quality management system, customer value, financial efficiency, commitment management, on company performance. The population of this study is the Iodized Salt Consumption Industry in Indonesia. The samples of this research are companies in Beryodim Salt Industry with an open organization scale and a CV which can be carried out by 12 companies. This research method uses the Structural Equation Model (SEM) which is operated using SmartPLS. This study produces a variable that the ISO 9001: 2015 quality management system, customer value, financial efficiency significantly affects company performance, while the variable management commitment directly has no significant effect on company performance.